Pearce, Monopoly and Socialism - Lancaster, Kelvin (Review of Economic Studies, 1955)
Journal Article Pearce, Monopoly and Socialism Get access Kelvin Lancaster Kelvin Lancaster London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 23, Issue 2, 1955, Pages 135–144, https://doi.org/10.2307/2296297 Published: 01 January 1955